PENYULUHAN PENGGUNAAN OBAT TRADISIONAL HABBATUSSAUDA UNTUK SISTEM IMUN DAN PENAMBAH DAYA INGAT BAGI SISWA MAN 2 KOTA MAKASSAR - Dhuha, Nur Syamsi; Tahar, Nurshalati; Leboe, Dwi Wahyuni; Wahyuddin, Munifah; Khaerani, Khaerani; Nonci, Faridha Yenny (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2023)
The use of black cumin as medicine or medicinal properties is in the seeds. The benefits of black cumin seeds are to treat various diseases such as strengthening the immune system, asthma, bronchitis, diabetes, increasing breast milk production, antihistamines or hypoallergenic, maintaining skin elasticity, antioxidants, antitumor, cancer, improving the digestive tract, antibacterial, lowering cholesterol and improve heart performance. In order to realize the degree of public health, it is necessary to carry out integrated and comprehensive health efforts in the form of individual health efforts and public health efforts. This community service aims to see how the level of knowledge of students at MAN 2 Makassar City about the use of Black Seed. Therefore, the results of this PKM show that it was synthesized by looking at the t count and t table for the two hypotheses. If (tcount) > ttable, then reject H0. Based on the analysis of the paired t test, if (tcount) is 4.86 and the ttable value for the two-way test is 2.11. Then, (t count) > ttable, then calculate H0 or in other words, that the means/average quiz results are significantly different from the means/average after being given counseling.